Rancangan e-LKPD Berbasis Collaborative Creativity Learning (CCL) Pokok Bahasan Perpindahan Kalor Pada Mesin Pembuatan Gula Pasir - Devita Syafa Adisti Putri; Sri Astutik; Firdha Kusuma Ayu Anggraeni (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2024)
Physics as a subject matter involves understanding concepts and mathematical applications that are often a challenge for students, for example the concept of heat transfer. To provide a memorable and interesting learning experience, the context of the e-LKPD design can be taken from everyday life, such as the process of making granulated sugar in a sugar factory. The process involves the concept of heat transfer, for example the stages of evaporation and crystallisation of neera. The purpose of this study was to analyse the validity of the design and learners' responses to the e-LKPD design. This type of research is development research with the ADDIE model and is limited to the development stage. Data collection involved literature study, observation, interviews, questionnaires, and documentation. The validation results obtained an average percentage value of 87.33%, with a very feasible category and learner responses showed a high level of interest, with a percentage value of 83%. Thus, e-LKPD based on collaborative creativity learning (CCL) on the subject of heat transfer in sugar making machines can be considered feasible and can be implemented effectively to students in learning activities.